Performance Measurement in a Custom Production Process Model Using the Process Mining Approach: A Systematic Literature Review - Wawa Wikusna; Mustafid; Ferry Jie (IEEE Access)
This study aims to explore and develop a method for measuring supply chain performance influenced by customer demand in custom product production. The research method used is a systematic literature review, focusing on measuring key indicators and evaluating supply chain performance. This study highlights the importance of Key Performance Indicators (KPIs) as an evaluation tool, which helps make decisions more effective and efficient in the supply chain. By using the Supply Chain Operation Reference (SCOR) model supported by the Analytic Hierarchy Process (AHP) and the normalization of the Snorm De Boer Score, this study shows a systematic measurement process from planning to evaluation. The results of the study indicate that supply chain performance measurement can provide guidance for companies to improve operational performance and support supply chain sustainability. The traffic light system is applied to identify performance indicators that require special attention, so that focused improvement recommendations can be provided. This study makes an important contribution to the development of supply chain performance management in the context of custom production.